Implementation Digital Financial Reports Using The Application For SIAPIK Contruction By Bank Indonesia - Oktavia, Lisa; Khusna, Putri Hidayatul; Surepno, Surepno (Pengabdian: Jurnal Abdimas, 2024)
The development of industrial technology In this era, the Indonesian economy progressed. However, there are still many MSMEs that fail to take advantage of current technological developments to manage their business management, especially financial management. Small, medium and micro businesses generally pay little attention to detailed and clear financial reports. Therefore, this research is expected to provide a reference for MSMEs to prepare financial reports. The purpose of this study is to provide an overview of the use of web-based and Android-based digital financial applications for financial management, especially daily financial reports with categories of sources of income and sources of expenditure. The implementation method is carried out in three ways, namely the MSMEs assisted KTNA 2 method, the training method and the mentoring method. This study aims to utilize digital finance to develop financial management in the KTNA assisted SIAPIK application. The results of the study show that MSMEs in Kudus Regency still don’t know much about digital finance. Financial bookkeeping carried out by KTNA 2 assisted MSMEs is still done manually, namely bookkeeping written in a book. Based on the results of the dedication, research found that MSMEs KTNA 2 Kudus Regency did not understand digital finance. Bookkeeping of MSMEs finance assisted by KTNA 2 is always done manually and recorded in the books. Therefore, one of Bank Indonesia’s assistance programs for KTNA 2 assisted MSMEs is implementing and teaching digital finance through the SIAPIK application.